The hexameter of Kristijonas Donelaitis’ Metai: potentials and limitations of an automated analysis - Meinhardt, Kierán (Baltistica, 2023)
This article subjects the Lithuanian hexameter epic Metai by Kristijonas Donelaitis to a detailed metrical examination. It describes an algorithmic approach to deriving the prosodical and metrical structure exclusively from the raw text of the digital edition. A statistical analysis confirms and further refines the earlier results pertaining to the types of hexameter used by Donelaitis. For the first time, robust quantitative results concerning the distribution and combination of caesuras can be obtained. The entire source code and data sets are published online for further exploration.
Keywords: Lithuanian; digital humanities; metrics; syllabification; quantitative methods; Kristijonas Donelaitis